The Gender-Equality Paradox in Intraindividual Academic Strengths: A Cross-Temporal Analysis - Balducci, Marco; Larose, Marie-Pier; Stoet, Gijsbert; Geary, David C. (SAGE Publications, 2025)
Independent of overall achievement, girls' intraindividual academic strength is typically reading, whereas boys' strength is typically mathematics or science. Sex differences in intraindividual strengths are associated with educational and occupational sex disparities in science, technology, engineering, and mathematics (STEM) fields. Paradoxically, these sex differences are larger in more gender-equal countries, but the stability of this paradox is debated. We assessed the stability of the gender-equality paradox in intraindividual strengths, and its relation to wealth, by analyzing the academic achievement of nearly 2.5 million adolescents across 85 countries and regions in five waves (from 2006 to 2018) of the Programme for International Student Assessment (PISA). Girls' intraindividual strength in reading and boys' strength in mathematics and science were stable across countries and waves. Boys' advantage in science as an intraindividual strength was larger in more gender-equal countries, whereas girls' advantage in reading was larger in wealthier countries. The results have implications for reducing sex disparities in STEM fields.